Analisis Penilaian Financial Performance Perusahaan Dengan Menerapkan Metode Economic Value Added, Financial Value Added dan Market Value Added Pada Perusahaan Telekomunikasi Yang Terdaftar di Bursa Efek Indonesia - Eri Triharyati; Beny Marselino; Yuli Eprianti; Yuli Nurhayati (PT Maju Malaqbi Makkarana, 2023)
Telecommunications companies that are still in competition demand companies that have good financial performance to attract outsiders to invest their capital. Company management in managing the business requires measurement of financial performance to evaluate the business. Financial performance can be measured using analytical tools in the form of financial ratios, the most commonly used to measure financial performance, financial value added performance, namely economic value added, financial value added and market value added, which takes into account the cost of capital paid by the company to determine whether company can create added value or not. The purpose of this research is to evaluate the company's financial performance by applying economic value added, financial value added and market value added methods. The research method used is a quantitative research method with a descriptive approach type. The results of the research show that the financial performance of PT. Telekomunikasi Indonesia, PT. XL Axiata and PT. Indosat, Tbk is reviewed through the EVA, FVA and MVA method approaches from 2018-2021 producing positive values or > 0 except for PT. XL Axiata in 2020 the EVA value produces a negative value. At PT. Only in 2018 did Smartfren Telecom produce positive EVA and FVA values, while MVA only in 2019 and 2020.